KEMAMPUAN SERBUK BIJI ASAM JAWA DALAM MENURUNKAN TSS, TURBIDITAS, DAN AMONIAK PENGOLAHAN LIMBAH CAIR PT. UTAMA MULTINIAGA INDONESIA - Dita Kartika; Nurjazuli Nurjazuli; Budiyono Budiyono (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Industrial liquid waste from waste clove cigarettes, washing waste and domestic waste. PT. Utama Multiniaga Indonesia still using alum to treat industrial cigarettes waste. In addition to having to pay a large alum spending around Rp 165,000,000.00/year, the use of alum continuously will cause a negative impact on the environment and human health. Therefore, the treatment needs alternative to a natural coagulant such as tamarind seed powder which can be obtained easily and cheap prices. This study aimed to analyze the ability of tamarind seed powder in lowering levels of TSS, turbidity and ammonia levels cigarette liquid waste by using One Way ANOVA. The samples used were 60 samples (30 protests and posttest 30) and sampling use grab sampling. This study showed that there are differences in levels of TSS and turbidity effluent cigarette between before and after administration of coagulant powder tamarind seeds. However, only a dose of 0.5 g/l to reduce levels of TSS and turbidity (p value 0,0001). A dose of 1.0 g/l, 1.5 g/l, 2.0 g/l and 2.5 g/l can increase levels of TSS and turbidity. All variations of doses can not lowered the levels of ammonia (p value 0,0001). It can concluded the optimum dose of coagulant powder tamarind seeds in lowering levels of TSS and turbidity of 0.5 gr/l.